The cost of fiscal policy uncertainty: Industry evidence of its impact on the labor market - J. Christina Wang (Federal Reserve Bank of Boston, 2013)
The anemic pace of the recovery of the U.S. economy from the Great Recession has frequently been blamed on heightened uncertainty, much of which concerns the nation's fiscal policy. Intuition suggests that increased policy uncertainty likely has different impacts on industries with different exposure to government actions. Such heterogeneity can help identify the effect of shocks due to policy uncertainty. This study uses industry data to explore whether policy uncertainty indeed affects the dynamics of employment during this recovery, and particularly whether it has a differential impact on employment across industries. This analysis focuses on heterogeneity across industries in terms of the fraction of their product demand that can ultimately be attributed to federal government expenditures. The estimation results reveal that policy uncertainty indeed retards employment growth more in industries that rely more heavily on federal government demand: the growth rate in the number of production employees in these industries appears to have been four-tenths of a percentage point lower during the quarters in recent years when policy uncertainty spiked. A similar impact is found for the growth of total employment, which also includes nonproduction employees. In addition, the evidence suggests that increased policy uncertainty renders firms more reluctant to adjust the number of employees in response to changes in output, a contributing factor to the sluggish recovery in employment. Moreover, this damping effect is stronger for industries with higher shares of output sold directly and indirectly to the federal government. By comparison, the adverse effect of heightened policy uncertainty on average weekly hours differs little across industries.
Keywords: D57; D80; E24; E66; G18; L50; 330; uncertainty; fiscal policy; input-output tables; industry accounts; employment; hours